Atopic dermatitis: Inside out or outside in? - Chan, Lawrence S.; Shi, Vivian Y. (2023)
The book explores one of the most common and challenging skin conditions, uniquely organized by intrinsic and extrinsic etiologies. Edited by Drs. Lawrence S. Chan and Vivian Y. Shi, with expert contributors, it analyzes the disorder’s pathophysiology and provides evidence-based, integrative management strategies. The book offers practical, targeted treatment recommendations through its Clinician’s Corner, discusses newly approved and emerging therapies, and addresses atopic comorbidities. Enhanced eBook access with full text, figures, and references is included.